Upaya Meningkatkan Nilai Karakter Kedisiplinan dengan Pembiasaan Baris Berbaris Peserta Didik Kelas V SD Negeri Kertosono Kecamatan Banyuurip Kabupaten Purworejo - Sugiyanto Sugiyanto; Victor Novianto (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to improve students' learning discipline by using the method of lining up habituation for fifth grade students of SD Negeri Kertosono. This type of research is classroom action research (CAR) which is carried out collaboratively, including action planning, action implementation, observation and reflection. The instruments used are non-test instruments in the form of teacher activity observation sheets, student activity observation sheets, teacher interview sheets, student learning discipline checklist sheets and field notes sheets. The data analysis technique used quantitative and qualitative analysis. Descriptive analysis technique of quantitative data is used to determine the percentage of students' learning discipline attitudes. The results of the discipline score using the line-of-sight habituation method showed that the students' learning discipline in each cycle increased after the action for two cycles. The percentage of students' discipline attitude. Based on the research, it shows that using the line-up habituation method can improve students' learning discipline. The percentage of students' learning discipline attitudes from the results of the disciplinary checklist also experienced a significant increase which was included in the very good category. It can be concluded that based on the results of the analysis above, learning using the line-of-sight habituation method can improve student learning discipline.